In situ Synthesis of Au-Induced Hierarchical Nanofibers/Nanoflakes Structured BiFeO3 Homojunction Photocatalyst With Enhanced Photocatalytic Activity - Li, Yan'an; Li, Jiao; Chen, Long; Sun, Haibin; Zhang, Hua; Guo, Hong; Feng, Liu (Frontiers in Chemistry, 2019)
In order to further improve the photocatalytic performance of BiFeO3 (BFO), novel Au-induced hierarchical nanofibers/nanoflakes structured BiFeO3 homojunctions (Aux-BFO, x = 0, 0. 6, 1.2, 1.8, 2.4 wt%) were in situ synthesized through a simple reduction method with assist of sodium citrate under the analogous hydrothermal environment. The effect of loading amount of Au nanoparticles (NPs) on the physicochemical properties and photocatalytic activity was investigated in detail. The Au1.2-BFO NFs sample show the best photocatalytic activity (85.76%), much higher than that for pure BFO samples (49.49%), mainly due to the hierarchical nanofibers/nanoflakes structured homojunction, the surface plasmon resonance (SPR) effect of Au NPs, as well as the presence of defects (Fe2+/Fe3+ pairs and oxygen vacancy). Furthermore, the possible formation mechanism of the unique homojunction and the enhanced photocatalytic mechanism for the degradation of methylene blue (MB) dye are proposed. It is proven that holes (h+) play the decisive role in the photocatalytic process. The present work provides a fascinating way to synthesize efficient homojunctions for the degradation of organic pollutes.